ANALISIS KEMAMPUAN OLAH DATA DAN ANALISIS DATA PRAKTIKUM FISIKA MAHASISWA - Nurhasana Siregar (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2023)
The ability to process data and analyze data is a must for students after doing practicum. This study aims to analyze the student's ability to analyze physics practicum data. This type of research is a qualitative research with data analysis using qualitative descriptive. Analyzing the ability of data processing and data analysis of physics practicum is observed from the results of work or practicum reports. The research sample is civil engineering students, totaling 26 people. The results showed that the ability of students to process data and analyze data was not good. The percentage of students' ability to analyze data using the linear regression method is 10%, and the ability to process repeated measurement data to determine direct error is 55% and indirect error is 5%. This is due to the lack of basic mathematical knowledge of students on exponentials, derivatives of mathematical operations, and not being able to convert non-linear physics equations into linear physics equations.